Flexural And Post-Fire Flexural Properties Of Eggshell Hybrid Glass Fibre Reinforced Polymer (Gfrp) Composites - Nithikorn Suvanamporn, Nithikorn (Universiti Sains Malaysia, 2019)
The use of polymer composite materials has increased considerably over the last decade. The unique properties of fibre reinforced composite materials enable their application in various technological areas such as space, aircraft, marine and automotive. Animal fibre of eggshell composites are considered to have potential use as reinforcing agents in polymer composite materials because of their principle benefits such as good strength and stiffness, low cost, and be an environmentally friendly, degradable, and renewable material. Chicken eggshells are crushed, ground and sieved for granules of size 75 μm for reinforcement in the matrix. Different types of composites are fabricated using (0,15,20) wt % of eggshell powder with E-glass fibre and epoxy matrix. Hand lay-up technique is adopted to fabricate epoxy glass composites with eggshell powder. After dispersing the eggshell powder in epoxy, the hardener is added which then will initiate cross-linking process. Then specimens are cured for 24 hours at room temperature. Post-fire and flexural properties of eggshell hybrid GFRP composites as a function of filler content in the particle sizes (75 μm) are investigated. The tests are conducted according to ASTM standards. Post-fire of the composites as a function of filler content examined for 2 minutes showed gradual reduction when the filler content increases because of the chemical composition and nature of egg shell. Experimental result has shown improvements in Flexural Modulus of this newly processed Eggshell Hybrid GFRP composite. Hence the development of epoxy/eggshell particulate composites material with good mechanical properties and light weight which is relevant to the engineering applications has the potential to be achieved.